2009
DOI: 10.1074/jbc.m807203200
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Solvent-exposed Tyrosine 74 on Cytochrome c Triggers Heme Iron-Methionine 80 Bond Disruption

Abstract: Cytochrome c, a mitochondrial electron transfer protein containing a hexacoordinated heme, is involved in other physiologically relevant events, such as the triggering of apoptosis, and the activation of a peroxidatic activity. The latter occurs secondary to interactions with cardiolipin and/or post-translational modifications, including tyrosine nitration by peroxynitrite and other nitric oxide-derived oxidants. The gain of peroxidatic activity in nitrated cytochrome c has been related to a heme site transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
135
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(144 citation statements)
references
References 70 publications
6
135
0
1
Order By: Relevance
“…Recent evidence points to cytochrome c as an intramitochondrial heme peroxidase after a conformational change triggered by binding to cardiolipin and indicates that this process is related to apoptotic signaling (68). We have found that the preferential nitration of cytochrome by peroxynitrite-derived radicals in one of the solvent-exposed tyrosine residues (Tyr-74) leads to a conformational change that causes the displacement of the sixth ligand to the heme (Met-80) and a gain in peroxidase activity (67); the conformational change induced by nitration in cells also facilitates its translocation to the cytosol (even in non-apoptotic cells) (69). The biological significance of these events is currently under investigation.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Recent evidence points to cytochrome c as an intramitochondrial heme peroxidase after a conformational change triggered by binding to cardiolipin and indicates that this process is related to apoptotic signaling (68). We have found that the preferential nitration of cytochrome by peroxynitrite-derived radicals in one of the solvent-exposed tyrosine residues (Tyr-74) leads to a conformational change that causes the displacement of the sixth ligand to the heme (Met-80) and a gain in peroxidase activity (67); the conformational change induced by nitration in cells also facilitates its translocation to the cytosol (even in non-apoptotic cells) (69). The biological significance of these events is currently under investigation.…”
mentioning
confidence: 89%
“…Other oxidizing and nitrating species tend to react with tyrosines other than Tyr-34 and do not lead to enzyme inactivation. Efforts have been also directed to understand how peroxynitrite-dependent nitration affects the redox properties of cytochrome c, an abundant mitochondrial protein and key partner of the electron transport chain (67). Recent evidence points to cytochrome c as an intramitochondrial heme peroxidase after a conformational change triggered by binding to cardiolipin and indicates that this process is related to apoptotic signaling (68).…”
mentioning
confidence: 99%
“…However, it has also been shown that peroxynitrite very slowly induces the nitration of the solvent-exposed Tyr74 residue of hhcytc in the absence of CL (the process takes 10 to 30 min). This leads to the cleavage of the Fe-Met80 bond, which is substituted by a weak Fe-Lys72 heme distal ligation (44).…”
Section: The Cl-bound Horse Heart Cytochrome C Displays Proapoptotic mentioning
confidence: 99%
“…[9] Thus, recent reports on the effects of protein nitration rely on the treatment of isolated proteins with this chemical. [10][11][12][13][14][15][16] In general, phenol rings are preferentially nitrated at ortho positions (e carbons in Tyr residues) relative to the hydroxyl group. Still, nitration could also take place at meta carbons, although the yield in this case is lower.…”
Section: Introductionmentioning
confidence: 99%